Learning Service Recommendations - Jungmann, Alexander; Kleinjohann, Bernd; Kleinjohann, Lisa (International Journal of Business Process Integration and Management 6(4))
The as a service paradigm reflects the fundamental idea of providing basic coherent functionality in terms of components that can be utilised on demand. These so-called services may also be interconnected in order to provide more complex functionality. Automation of this service composition process is indeed a formidable challenge. In our work, we are addressing this challenge by decomposing service composition into sequential decision making steps. Each step is supported by a recommendation mechanism. If composition requests recur over time and if evaluations of composition results are fed back, a proper recommendation strategy can evolve over time through learning from experience. In this paper, we describe our approach of modelling this service composition and recommendation process as Markov decision process and of solving it by means of reinforcement learning. A case study serves as proof of concept.

Systematic Application of UCIS to Improve the Automation on Verification Closure - Kuznik, Christoph; Oliveira, Marcio F.; Defo, Bertrand; Müller, Wolfgang (Proceedings of DVCON)

A 3D Path Planning Approach Extended by Bifurcation Theory for Formation Flights - Rasche, Christoph; Stern, Claudius; Kleinjohann, Lisa; Kleinjohann, Bernd (Recent Advances in Robotics and Automation, Studies in Computational Intelligence, Band 480)
After big disasters, search and rescue missions take place. During these missions it is essential to obtain an overview of the overall situation to arrange efficient rescue tasks as soon as possible. Afterwards, this information has to be continuously updated during the complete mission in order to quickly respond to changing conditions. The use of unmanned aerial vehicles (UAVs) is a viable choice to obtain such an overview in a fast and efficient way. Using multiple UAVs, the problem of coordination has to be solved to decrease the time needed to explore an area. We present an approach for the coordination of UAVs by setting up formation patterns using bifurcation theory. We combine this theory with a potential field approach for exploration, based on harmonic functions.

Fault-Tolerant Deployment of Real-Time Software in AUTOSAR ECU Networks - Klobedanz, Kay; Jatzkowski, Jan; Rettberg, Achim; Müller, Wolfgang (International Embedded Systems Symposium (IESS) 2013)

Automatic Reconstruction of Polygonal Room Models from 3D Point Clouds - Mertsching, Bärbel; Divband Soorati, Mohammad; Kotthauser, Tobias (IEEE International Conference on Robotics and Biomimetics (ROBIO))

Time delay implies cost on task switching: A model to investigate the efficiency of task partitioning - Hamann, Heiko; Karsai, Istvan; Schmickl, Thomas (Bulletin of Mathematical Biology)

Algorithmic Requirements for Swarm Intelligence in Differently Coupled Collective Systems - Hamann, Heiko; Schmickl, Thomas; Stradner, Jürgen; Crailsheim, Karl; Thenius, Ronald; Zahadat, Payam (Chaos, Solitons & Fractals)

Virtual Spatiality in Agent Controllers: Encoding Compartmentalization - Hamann, Heiko; Schmickl, Thomas; Stradner, Jürgen; Schwarzer, Christopher; Michiels, Nico K.; Esparcia-Alcazar, Anna Isabel (Applications of Evolutionary Computation - 16th European Conference (EvoApplications 2013))

A Reductionist Approach to Hypothesis-Catching for the Analysis of Self-Organizing Decision-Making Systems - Hamann, Heiko (7th IEEE Int. Conf. on Self-Adaptive and Self-Organizing Systems (SASO 2013))

Speciation Dynamics: Generating Selective Pressure Towards Diversity - Hamann, Heiko; Lio, Pietro; Miglino, Orazio; Nicosia, Giuseppe; Nolfi, Stefano; Pavone, Mario (12th European Conference on Artificial Life (ECAL 2013))

Towards Swarm Calculus: Urn Models of Collective Decisions and Universal Properties of Swarm Performance - Hamann, Heiko (Swarm Intelligence)

Themenmodellierung zur Identifikation und Gruppierung von Spam-Webseiten - Laudemann, Stefan

Nichtapproximierbarkeitsresultate zu Radius- und Durchmesserclustering unter Verwendung von L_p-Metriken - Leder, Lennart

A heuristic energy-aware approach for hard real-time systems on multi-core platforms - He, Da; Müller, Wolfgang (Microprocessors and Microsystems - Embedded Hardware Design 37(6-7))

Embedded Systems: Design, Analysis and Verification. Proceedings of the 4th IFIP TC10 International Embedded Systems Symposium, IESS 2013, Paderborn, Germany, June 2013

Organic Programming of Real-Time Operating Systems - Khaluf, Lial; Rammig, Franz-Josef (The Ninth International Conference on Autonomic and Autonomous Systems)

Methods for the Design and Development - Anacker, Harald; Dellnitz, Michael; Flaßkamp, Kathrin; Grösbrink, Stefan; Hartmann, Philip; Heinzemann, Christian; Horenkamp, Christian; Kleinjohann, Lisa; Kleinjohann, Bernd; Korf, Sebastian; Krüger, Martin; Müller, Wolfgang; et al. (Design Methodology for Intelligent Technical Systems Systems – Develop Intelligent Technical Systems of the Future)

Learning Efficient Information Extraction on Heterogeneous Texts - Wachsmuth, Henning; Stein, Benno; Engels, Gregor (Proceedings of the Sixth International Joint Conference on Natural Language Processing)

Information Extraction as a Filtering Task - Wachsmuth, Henning; Stein, Benno; Engels, Gregor (Proceedings of the 22nd ACM International Conference on Conference on Information & Knowledge Management)

Automatic Pipeline Construction for Real-Time Annotation - Wachsmuth, Henning; Rose, Mirko; Engels, Gregor (14th International Conference on Intelligent Text Processing and Computational Linguistics)